Pengaruh Financial Stability, External Pressure, dan Rationalization Terhadap Financial Statement Fraud - Ikram Muhammad Faris; Satiman (GLOBAL SCIENTS PUBLISHER, 2025)
This study aims to determine the effect of financial stability, external pressure, and rationalization on financial statement fraud (Empirical Study of Infrastructure Sector Companies Listed on the Indonesia Stock Exchange for the 2019-2023 Period) both partially and simultaneously. This type of research is quantitative. The sample in this study was obtained using purposive sampling technique, so that 14 samples were obtained with the 2019-2023 research period. The data used in this study were obtained from financial statements. The tests used in this study are descriptive statistikal tests, selection of panel data regression estimation models, classical assumption tests, and hypothesis testing. The results of this study indicate that based on partial tests external pressure, and rationalization have an effect on financial statement fraud, but financial stability has no effect on financial statement fraud. Based on simultaneous tests, financial stability, external pressure, and rationalization have an effect on financial statement fraud.